TANTANGAN GURU DALAM MENGAJAR BAHASA ARAB DI SALAFIYYAH ULA ICBB YOGYAKARTA: STUDI DESKRIPTIF TENTANG STRATEGI DAN MOTIVASI BELAJAR SANTRI - Aini, Hafidza Azzahra Qurrota; Istiqomah, Istiqomah; Mulyani, Sri; Wardani, Widyaningtyas Kusuma (STKIP Pesisir Selatan, 2025)
Various challenges faced by Arabic language teachers at the elementary level, particularly at Salafiyyah Ula Islamic Centre Bin Baz (ICBB) Yogyakarta, form the foundation of this research. At this institution, Arabic serves as the primary medium of instruction; however, the teaching process still encounters significant difficulties such as diverse student abilities, limited instructional time, inadequate learning media, and a lack of student motivation. The objectives of this study are to identify the challenges faced by teachers, analyze the instructional approaches employed, and examine the teachers’ efforts to enhance students’ motivation to learn Arabic. Data were collected through observation, interviews, and questionnaires distributed to Arabic language teachers. This study employed a qualitative descriptive method, and the data were analyzed using thematic analysis techniques involving data reduction, presentation, and conclusion drawing, with source triangulation used to ensure validity. The findings reveal that teachers face both pedagogical and technical problems, including students’ varying levels of comprehension and insufficient learning facilities. To overcome these challenges, teachers have adopted innovative strategies such as language games, vocabulary memorization (mufrodat), and individualized learning approaches. Although technology has not been fully utilized, these strategies have successfully increased students’ engagement and learning motivation.